Agmatine Reverses Sub‐chronic Stress induced Nod‐like Receptor Protein 3 (NLRP3) Activation and Cytokine Response in Rats. Issue 4 (10th May 2016) - Sahin, Ceren; Albayrak, Ozgur; Akdeniz, Tuğba F.; Akbulut, Zeynep; Yanikkaya Demirel, Gulderen; Aricioglu, Feyza
Abstract: The activation of Nod‐like receptor protein 3 (NLRP3) has lately been implicated in stress and depression as an initiator mechanism required for the production of interleukin (IL)‐1β and IL‐18. Agmatine, an endogenous polyamine widely distributed in mammalian brain, is a novel neurotransmitter/neuromodulator, with antistress, anxiolytic and antidepressant‐like effects. In this study, we examined the effect of exogenously administered agmatine on NLRP3 inflammasome pathway/cytokine responses in rats exposed to restraint stress for 7 days. The rats were divided into three groups: stress, stress+agmatine (40 mg/kg; i.p.) and control groups. Agmatine significantly down‐regulated the gene expressions of all stress‐induced NLRP3 inflammasome components (NLRP3, NF‐κB, PYCARD, caspase‐1, IL‐1β and IL‐18) in the hippocampus and prefrontal cortex (PFC) and reduced pro‐inflammatory cytokine levels not only in both brain regions, but also in serum. Stress‐reduced levels of IL‐4 and IL‐10, two major anti‐inflammatory cytokines, were restored back to normal by agmatine treatment in the PFC. The findings of the present study suggest that stress‐activated NLRP3 inflammasome and cytokine responses are reversed by an acute administration of agmatine. Whether antidepressant‐like effect of agmatine can somehow, at least partially, be mediated by the inhibition of NLRP3 inflammasome cascade and relevant inflammatory responses requires further studies in animal models of depression.